2020
DOI: 10.1038/s41586-020-2668-z
|View full text |Cite
|
Sign up to set email alerts
|

Structure of hepcidin-bound ferroportin reveals iron homeostatic mechanisms

Abstract: The serum iron level in humans is tightly controlled by the action of the hormone hepcidin on the iron efflux transporter ferroportin. Hepcidin regulates iron absorption and recycling by inducing ferroportin internalization and degradation 1 . Aberrant ferroportin activity can lead to diseases of iron overload, like hemochromatosis, or iron limitation anemias 2 . Here, we determined cryogenic electron microscopy (cryo-EM) structures of ferroportin in lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
217
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(224 citation statements)
references
References 83 publications
6
217
0
1
Order By: Relevance
“…In addition, we have made selective deletion constructs that exhibit improved thermal stability in solution and largely retain iron‐transport activity in vitro . During the review process of this manuscript, the structure of human Fpn was published [25]. Whilst this provides an important advancement, the detailed transport mechanism remains unresolved.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have made selective deletion constructs that exhibit improved thermal stability in solution and largely retain iron‐transport activity in vitro . During the review process of this manuscript, the structure of human Fpn was published [25]. Whilst this provides an important advancement, the detailed transport mechanism remains unresolved.…”
Section: Discussionmentioning
confidence: 99%
“…These remain to be investigated experimentally, but of note, Rishi and colleagues recently reported on the intracellular localization of ferroportin dimers, and concluded that both the carboxy-and amino-termini of the protein are intracellular [109]. As cited earlier, the details of hepcidin's own interaction sites with ferroportin remain the subject of different structural determination projects [12,18,108]. Relatedly, and of interest, Neves and colleagues, using experiments on iron overload in European bass (Dicentrarchus labrax), have discussed the functional partnership between hepcidin and ferroportin from an evolutionary perspective and suggested that this may "open new possibilities for the pharmaceutical use of selected fish […] hepcidins during infections, with no impact on iron homeostasis" [90,91].…”
Section: Potential Leads For Coronavirus Research Hepcidin-like Motifmentioning
confidence: 99%
“…Finally, hepcidin binds to and mediates the degradation of ferroportin (encoded by the SLC40A1 / FPN1 gene), the only known cellular iron exporter. The structural details of this interaction are being mapped and studied in ever more detail [18,88,108].…”
Section: The Hepcidin Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…FPN activity is decreased by the liver-derived hormone hepcidin. Recent studies highlight that hepcidin degrades FPN loaded with iron by binding to a specific cavity located between the N and C domains, thus blocking iron efflux and inhibiting its transport [ 69 ]. This results in an overall reduction of iron in the bloodstream [ 70 ].…”
Section: Intracellular Iron Metabolismmentioning
confidence: 99%